Abilities contributing to the critical thinking through the teaching process of the history of Brazil - Batista De Faria Junior, João; González González, Margarita; Alvarez Mesa, Yuniesky (Atenas, 2016)
The development of abilities contributing to critical thinking in the teaching-learning process of the history of Brazil is an essential component in the Program of Youth and Adult Education, taking into account the characteristics of this type of program and the role students are called to play in society, while assuming social, economic and political responsibilities. Therefore, in order to characterize its development, the analysis of the level of development of cognitive and affective-behavioral dimensions is required, as essential elements of the present study.